A syringe adapter for reduced muscular strain and fatigue. (May 2020) - Ulbrich, Joseph; Swader, Robert; Petry, George; Cox, Benjamin L.; Greene, Runyu L.; Eliceiri, Kevin W.; Radwin, Robert G.
Abstract: Workers in hospitals, clinics, and contract research organizations who repetitively use syringes have an increased risk for musculoskeletal disorders. This study developed and tested a novel syringe adapter designed to reduce muscle strain associated with repetitive fluid draws. Three syringe plunger extension methods (ring-finger, middle-finger, and syringe adapter) were studied across twenty participants. Electromyogram signals for the flexor digitorum superficialis and extensor digitorum muscles were recorded. The syringe adapter required 31% of the 90th percentile flexor muscle activity as compared to the ring-finger syringe extension method, and 45% the 90th percentile flexor muscle activity as compared to the middle-finger method (p < 0.001). The greatest differences were observed when the syringe was near full extension. Although the syringe adapter took more time than the other syringe extension methods (1.5 times greater), it greatly helped reduce physical stress associated with repetitive, awkward syringe procedures. Highlights: The syringe adapter required less muscle activity than conventional methods. Muscle activity increased for conventional methods as the syringe extends. Muscle activity did not increase for the adapter as the syringe extended. The syringe adapter required more time than the conventional methods.